(untitled) (AYUSHDHARA, 2018)
Neck pain is one of the most frequent musculoskeletal cause of consultation in primary care worldwide. Disc degeneration is the main contributing pathology for many cervical spine complications. Development of myelopathy and compression further leads to more complications. Manyastambha can be correlated with cervical spondylosis due to similar clinical presentation. Manyasthamba, Vata vyadhi by its nature with the symptoms such as pain and stiffness is pacified through Vata Kapha management. Nasya with Taila pacifies the Vata Kapha mainly the Vata. Bhringaraja Taila Nasya is a Snehana kind of Navana Nasya and having property of Tridoshahara, Balya, Rasayana, Vrushya, Vedanasthapaka and Srothoshodhaka. Vishwadi Dwadashanga kwatha is having property of Vata shamana. Hence these drugs were considered in this study. A total of 30 patients were randomly selected from OPD and IPD of D.G.M.A.M.C. and Hospital and Research centre camps conducted by the collage/Hospital after fulfilling the inclusion and exclusion criteria. All 30 patients were randomly divided in 3 groups. It was comparative clinical trial. In Group A- 10 patients were given Maha Bhringaraja Taila Nasya for 7 days. In Group B-10 patients were given Vishvadidwadashanga Kwatha internally for 14 days. In Group C- 10 patients were given both Maha Bhringaraja Taila Nasya for 7 days and Vishvadidwadashanga Kwatha for 14 days. Subjective and objective parameters of base line data to after treatment data were compared for the assessment of results by using ‘Annova’ test. Results shows that Group A patients, treated with Maha Bringaraja Taila were showed better improvement than the Group B patients treated with Vishwadidwadashanga kwath.